Solar radiation and temperature measurement of solar dish concentrator system - Rafeeu, Yaaseen; Ab Kadir, Mohd Zainal Abidin; Abdullah, Senan Mahmood; Adam, Nor Mariah (David Publishing Company, 2010)
Concentrating solar power (CSP) technologies could be one of the major contributor to worlds future energy needs and which would be cheap and clean sources of energy. This would improve energy utilization, higher conversion efficiency with reliable and affordable supply of electricity to the public. The proposed approach is using 18 inch diameter of solar dish concentrator to measure the solar radiation using the aluminium foil as a reflector. In this paper, solar radiation is collected to investigate the solar fraction on incoming solar energy in wet climate.